Leaving no-one behind in the workplace health promotion: towards regulatory equity in the Ecuadorian micro-enterprises - Gómez-García, Antonio R.; Hacay Chang, Alywin; Valenzuela-Mendieta, Richard Oswaldo; García-Arroyo, José A. (Journal of Public Health Policy, 2024)
The purpose of workplace public health programmes and regulations is to promote safety and health for the entire working population nationwide. Some countries limit the scope of such programmes to medium or big-sized companies, leaving out small and micro-enterprises, thus discriminating against many workers exposed to risks. This Viewpoint aims to identify inequalities in occupational health generated by the new Regulation for Workplace Health Promotion (WHP) in Ecuador. We showed how the regulation excludes all micro-enterprises and displayed the essential role of micro-enterprises in the business fabric and the Ecuadorian labour market. More than 93% of the registered companies are micro-enterprises and these include more than 25% of the employees in the formal economy. Integrating occupational health into the public health system will require deep analysis to improve protection for the working population.
Keywords: workplace health promotion; public health policy; Ecuadorian micro-enterprises; Scopus; JCR